Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Consider the second order ODE (actually it is time-independent Schrödinger equation)

$$\frac{d^2\phi}{dx^2} + V(x)\phi = E\phi$$

We know that $\phi$ is a bound solution. This means the following two things:

(i)$$\lim_{x\to \pm\infty}\phi(x)=0 .$$

(ii) $0<E<\max[V(x)]$.

Using this information, can we prove

$$\int_{-\infty}^{\infty}\vert\phi\vert^2\frac{dV}{dx} dx=0\,?$$

You are free to make any reasonable assumptions about the nature of $V(x)$ and $\phi(x)$ along your way.

share|cite|improve this question
Try doing by-parts integration twice. And nice name. – anon Nov 17 '11 at 19:40
up vote 2 down vote accepted

If you assume that the potential $V(x)$ is bounded, then we can prove it by integration by parts as suggested by anon: $$ \int^\infty_{-\infty}\phi^2\frac{dV}{dx}{dx}=\int^\infty_{-\infty}\phi^2dV =\phi^2V\,\big|^\infty_{-\infty}-2\int^\infty_{-\infty}V\phi\frac{d\phi}{dx}dx $$ where the last equality follows from integration by parts. Since $\lim_{x\to \pm\infty}\phi(x)=0$ by your assumption and $V(x)$ is bounded by my assumption, $\phi^2V\,\big|^\infty_{-\infty}=0$. Now using the equation $\frac{d^2\phi}{dx^2} + V(x)\phi = E\phi$, we can rewrite the above equation as $$ \int^\infty_{-\infty}\phi^2\frac{dV}{dx}{dx}=-2\int^\infty_{-\infty}V\phi\frac{d\phi}{dx}dx=2\int^\infty_{-\infty}\frac{d^2\phi}{dx^2}\frac{d\phi}{dx}dx-2E\int^\infty_{-\infty}\frac{d\phi}{dx}dx:=I+II. $$ Note that $$I=2\int^\infty_{-\infty}\frac{d^2\phi}{dx^2}\frac{d\phi}{dx}dx=2\int^\infty_{-\infty}\frac{d\phi}{dx}d\big(\frac{d\phi}{dx}\big)=\big(\frac{d\phi}{dx}\big)^2\Big|^\infty_{-\infty}=0$$ since $\lim_{x\to \pm\infty}\phi(x)=0$ implies that $\lim_{x\to \pm\infty}\frac{d\phi}{dx}(x)=0$. Note also that $$II=-2E\int^\infty_{-\infty}\frac{d\phi}{dx}dx=-2E\phi\,\big|^\infty_{-\infty}=0.$$ Now the result follows.

Note added: To see that $\lim_{x\to \pm\infty}\frac{d\phi}{dx}(x)=0$, first note that $\frac{d\phi}{dx}$ is bounded. To see this, since $\frac{d^2\phi}{dx^2} + V(x)\phi = E\phi$, $\lim_{x\to \pm\infty}\phi(x)=0$ and $V(x)$ is bounded, we have $\lim_{x\to \pm\infty}\frac{d^2\phi}{dx^2}=0$. This implies that $\frac{d\phi}{dx}$ is bounded. Next, if we multiply $\phi$ to $\frac{d^2\phi}{dx^2} + V(x)\phi = E\phi$, we get $$\phi\frac{d^2\phi}{dx^2}=(E-V(x))\phi^2$$ Now integrate it from $M$ to $\infty$ and we get $$\int_M^\infty\phi\frac{d^2\phi}{dx^2}dx=\int_M^\infty(E-V(x))\phi^2dx.$$ The right hand side is zero when $M$ tends to infinity since $V(x)$ is bounded and the eigenfunction $\phi$ is $L^2$. On the other hand, by integration by parts, the left hand side is $$\int_M^\infty\phi\frac{d^2\phi}{dx^2}dx=(\phi\frac{d\phi}{dx})\Big|^\infty_M-\int_M^\infty(\frac{d\phi}{dx})^2dx=-\phi(M)\frac{d\phi}{dx}(M)-\int_M^\infty(\frac{d\phi}{dx})^2dx.$$ The first term goes to zero since $\lim_{x\to \pm\infty}\phi(x)=0$ and $\frac{d\phi}{dx}$ is bounded. Combining all these, we have $\lim_{x\to \infty}\frac{d\phi}{dx}(x)=0$. Similarily we can prove that $\lim_{x\to -\infty}\frac{d\phi}{dx}(x)=0$.

share|cite|improve this answer
Paul, thank you so much. Just a follow up question: How does $$\lim_{x\to\pm\infty}\phi(x)=0$$ imply $$\lim_{x\to\pm\infty}\frac{d\phi(x)}{dx}=0?$$ – anon Nov 21 '11 at 21:14
see my edited answer. – Paul Nov 26 '11 at 7:21
Paul thanks for the rigorous explanation – anon Nov 28 '11 at 22:02
You are welcome. You may want to accept the answer. – Paul Nov 29 '11 at 13:27

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.